'Imagined San Francisco': Unpacking Urban Regime Theory through Interactive Cartography. Issue 1 (March 2017) - Howell, Ocean
Abstract : American urban historians have begun to understand that digital mapping provides a potentially powerful tool to describe political power. There are now important projects that map change in the American city along a number of dimensions, including zoning, suburbanization, commercial development, transportation infrastructure, and especially segregation. Most projects use their visual sources to illustrate the material consequences of the policies of powerful agencies and dominant planning 'regimes.' As useful as these projects are, they often inadvertently imbue their visualizations with an aura of inevitability, and thereby present political power as a kind of static substance–possess this and you can remake the city to serve your interests. A new project called 'Imagined San Francisco' is motivated by a desire to expand upon this approach, treating visual material not only to illustrate outcomes, but also to interrogate historical processes, and using maps, plans, drawings, and photographs not only to show what did happen, but also what might have happened. By enabling users to layer a series of historical urban plans–with a special emphasis on unrealized plans–'Imagined San Francisco' presents the city not only as a series of material changes, but also as a contingent process and a battleground for political power.